Potential of oil palm trunk starch as flocculant for contaminant of emerging compound removal. Issue 1 (August 2021) - Mohd Amin, M F; Mat Rasat, M S; Ahmad, M I; Aftar Ali, N S; Muda, K; Zaidi, N S; Ismail, S; Mohamad Shahimin, M F; Mohd Amin, M A; Salam, M A
Abstract: In this preliminary study, a natural flocculant is developed from an oil palm trunk. The flocculant further tested for its ability in turbidity and COD removal with additional of atrazine in wastewater and demineralised water matrix. At the optimum dosage of 20mg/L, the developed cationic OPT starch able to remove around 95% turbidity and 85% COD. In addition, the cationic OPT starch also show the ability to remove spiked atrazine from both water matrixes to the maximum range of 55-85%. In conclusion, the developed oil-palm based flocculant show great potential for real-world application with added cost-effective benefits.